2011
DOI: 10.1016/j.bmc.2011.06.050
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of select kahalalide F analogs with antitumor and antifungal activities

Abstract: Kahalalide F (KF) and the regioisomer isoKF are novel anticancer drugs of marine origin and currently under clinical investigation. Here we report the synthesis of two new KF analogs with significant in vitro and in vivo antifungal and antitumor activities. The primary amine hydrogen of ornithine in KF has been replaced with 4-fluoro-3-methylbenzyl and morpholin-4-yl-benzyl via reductive N-alkylation. The TGI of these analogs using the NCI-60 cell line screening revealed promising results when compared to pacl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…These compounds displayed antifungal activities against C. albicans and C. neoformans both in vitro and in vivo (Shilabin and Hamann 2011). …”
Section: Antifungal Productsmentioning
confidence: 99%
“…These compounds displayed antifungal activities against C. albicans and C. neoformans both in vitro and in vivo (Shilabin and Hamann 2011). …”
Section: Antifungal Productsmentioning
confidence: 99%
“…Of the hundreds of KF analogues produced by different research groups, only two modifications on the L -Orn residue showed a similar or higher potency in selected cancer cell lines. [14],[15] Perhaps it will be necessary to reconsider the KF modification approach focusing on improving the short half-life instead of increasing its potency. Much has been learned about the optimization of half-life, metabolism and bioavailability from the 15 year journey leading to the development for capsofungin (Cancidas®), the first in class antifungal derived from the echinocandins.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has modified natural KF at the Orn- residue which yielded two molecules with a similar or higher potency in selected cancer cell lines. [14],[15] In this report we provide an approach to produce modified KF analogues with additional amino acid residues on the N- terminal side chain after removal of the terminal fatty acid by selective hydrolysis between threonine and valine.…”
Section: Introductionmentioning
confidence: 99%
“…The original discoverer of this group of compounds published an interesting paper on selected kahalalide F analogs with antitumor and antifungal activities in 2011 [87], and recently in the middle of 2012, PharmaMar stopped development of the kahalalide derivative 1-[ N -[(4 S )-4-methyl-1-oxohexyl]- d -valine]-kahalalide F which they were developing as an antitumor agent under the generic name elisidepsin and trade name of Irvalec ® [82], even though it had activity in gastroesophageal tumors. This appeared to be a business decision due to the very low numbers of potential patients.…”
Section: Other Marine-derived Compounds In Clinical Trials Againstmentioning
confidence: 99%